Benefits accruing to Iraq and its national carrier upon ratification - Rian Hashim Hamdoon, Raed Ahmed Khalil, Mohanad Hamad Ahmed, (Opción, 2019)
This study provides an overview of the new changes made in the Montreal Convention which led to significant benefits for consumers in the civil aviation sector. For this purpose, the analytical method is used in this study by analyzing the provisions of the Montreal Convention. The study found that the liability regime of this convention overcomes the problems resulting from the liability limits in the Warsaw Convention. And the researchers conclude that it is necessary for the Iraqi government to ratify the Montreal Convention which guarantees better protection for consumers of air transport service.